2022
DOI: 10.1590/fst.45221
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of industrialized and artisanal Minas fresh cheese commercialized in the Federal District, Brazil

Abstract: The aim of this study was to evaluate the microbiological quality of Minas fresh cheese commercialized in Federal District, Brazil. For this, 20 samples of industrialized cheeses were collected in supermarkets and 20 samples of artisanal cheeses were collected in public food markets. The analyzes performed were total count of bacteria, determination of coliforms, count of S. aureus and identification of Salmonella spp. (InvA gene) and S. aureus (SeC gene). The results showed that 26 samples (65%) were unfit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Cheese is among the most consumed dairy products, corresponding to 14% of the world's consumption (Siqueira & Schettino, 2021). In addition, it is associated with health benefits once it is considered a source of vitamins (A, B2 and B12), minerals (calcium and phosphorus) and proteins (Rodrigues et al, 2022). Recent studies have shown that all these nutrients together may reduce the potential risk of cardiovascular diseases (Feeney et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cheese is among the most consumed dairy products, corresponding to 14% of the world's consumption (Siqueira & Schettino, 2021). In addition, it is associated with health benefits once it is considered a source of vitamins (A, B2 and B12), minerals (calcium and phosphorus) and proteins (Rodrigues et al, 2022). Recent studies have shown that all these nutrients together may reduce the potential risk of cardiovascular diseases (Feeney et al, 2021).…”
Section: Introductionmentioning
confidence: 99%